Laser-Induced Graphene Oxide on Polyimide Sheet: The Effect of Current Regulation on the Laser Power Stability - Martila, Lenny Intan; Suryadi, Suryadi; Nursidik Yulianto; Yuliati Herbani; Isnaeni, Isnaeni; Supardi, Zainul Arifin Imam; Suaebah, Evi; Iyon Titok Sugiarto (Universitas Negeri Surabaya, 2024)
Graphene oxide is a two-dimensional substance that shares the same structure as graphene and can be produced using several methods. The difficulty for green technology lies in developing a cost-effective and efficient method to produce graphene and graphene oxide without relying on chemical processes. A highly sustainable technology involves the use of a laser diode, which is both cost-effective and environmentally friendly. This technique produces a material known as laser-induced graphene/graphene oxide (LIG/LIGO). From a commercial standpoint, the laser diode is typically purchased without an electronic stabilizer component. Nevertheless, laser stability is crucial for the production process of LIG/LIGO. The objective of our study is to examine the impact of laser current management on the production of graphene on a polyimide (PI) sheet utilizing a 450 nm diode laser. The laser controller we utilize is the National Instruments (NI) PXIe-1085 device. The optical power of the laser diode was measured between 0.21 and 0.79 W. After the laser current was stabilized, the power slightly shifted, ranging from 0.18 to 0.86 W. Both experiments were conducted with a current range of 0.3 to 1 A. Before regulation, the laser diode experiences current fluctuations in the range of around 0.01 to 0.03 A. The study findings highlight the significance of laser current management in manufacturing LIG/LIGO by ensuring a consistent and precise laser power output, hence minimizing flaws in the final product. However, the analysis reveals that graphene oxide is the predominant yield in this characterization. This fact is caused by the presence of a graphene layer not exposed to the surface during measurement. This approach provides several benefits, such as the capacity to produce graphene/GO in a targeted, non-chemical, and fast manner, as well as its potential for diverse applications.